A study on early detection of sewer pipeline blockage using CCD tomography approach. Issue 1 (January 2021) - Jamaludin, J; Rahim, R A; Rahiman, M H F; Ismail, W Z W; Ismail, I; Sahrim, M; Balakrishnan, S R; Raisin, S N; Rahalim, F M; Naeem, B
Abstract: In a sewage system, congealed mass is created by mixing non-biodegradable solid matter with fat, oil and grease. Congealed mass might cause a sewer blockage and overflow. This issue may impose a risk to public health and environment. It also leads to increased operational and maintenance costs of sewer system. A robust and durable sensor system are required to monitor the sewer network blockage which could cause a fluctuation in the data. CCD tomography approach will be used to detect the congealed mass forming in sewer network at early stage. The main concept of CCD tomography approach is to analyze the structure and composition of congealed mass by examining the light intensity after penetrated. Therefore, the location and size of the sewer blockage can be predicted. Light reflection from the congealed mass will strikes onto CCD surfaces. This light source will be converted into an electrical signal which is in voltage output value. Filtered images of Linear Back Projection (LBP) algorithm will be applied to reconstruct the image and identify the characteristic of congealed mass either fat, oil or grease. The location and the size of the congealed mass forming also can be identified using this CCD tomography approach.